190 Haem and carbon monoxide (co) modulation of large-conductance ca2+-activated k+ (bk) channel activity. (5th June 2017) - Ayeni, Modupe; Kapetanaki, Sofia; Raven, Emma; Storey, Nina; Davies, Noel
Abstract : Haemolysis is a distinctive feature of certain diseases such as haemorrhagic stroke and sickle cell anaemia. The haem released from red blood cells during haemolysis can build up to toxic levels producing further complications such as cell and tissue damage. Intracellular haem concentration is mainly regulated by haem oxygenase (HO) enzymes which degrade haem to carbon monoxide (CO) and other molecules. Nevertheless, the high haem concentrations during haemolytic diseases can saturate the HO system potentially increasing concentrations of both CO and free haem. Arterial smooth muscle cells (SMCs) express a variety of ion channels including large-conductance Ca 2+ -activated K + (BK) channels. Activation of BK channels produce spontaneous transient outward currents (STOCs) which hyperpolarize SMCs resulting in cell relaxation and vasodilation. Therefore, BK channels have a negative feedback role to limit SMC contraction. Intracellular haem has been reported to inhibit single BK channel activity whereas CO has been shown to produce stimulatory effects. However, little is known about the effects of haem and CO on STOCs or whole-cell BK currents. The aim of this study is to investigate the effects of haem and CO on STOCs. SMCs were isolated from the mesenteric artery of male Wistar rats. Single BK channel currents and STOCs were recorded using excised (inside-out) and perforated whole-cell patch techniques respectively. CO was applied using CO-releasing molecule 3 (CORM-3) which was prepared before each use. Data are presented as mean± SEM and statistical analyses were performed using paired and unpaired Students T-test as appropriate. Consistent with previous reports, application of haem (100 nM) to the cytoplasmic side of inside-out patches reduced BK channel activity to 4.7 × 10 -3 ±3.4×10 -3  times that of control (n=4, p<0.05) whereas CORM-3 (30 µM) increased channel activity by 5.7±0.4 fold (n=8, p<0.05) at low [Ca 2+ ]i (300 nM). Surprisingly, during perforated whole-cell recordings, extracellular haem (5 µM) increased STOC amplitude by 16% (1.16±0.04, p<0.05, n=3). This effect was further enhanced in the presence of the HO-inhibitor, zinc protoporphyrin-IX (ZnPP-IX) (1.4±0.1, p 0.01, n=4). Extracellular application of CORM-3 (30 µM) increased STOC frequency (1.81±0.26, p<0.01, n=8) without significantly affecting STOC amplitude. In summary, the stimulatory effects of haem on STOCs contradict excised patch data. This suggests that the effects of haem might be influenced by intracellular components which are absent in excised patches. Results from ZnPP-IX studies further imply that the effects of haem on STOCs might be mediated independent of its degradation product, CO. Therefore, information gained from further studies could improve our understanding of the vascular changes that occur during haemolytic diseases.